Gendered globalization: The relationship between globalization and gender gaps in employment and occupational opportunities - Yoav Roll; Moshe Semyonov; Hadas Mandel (Luxembourg Income Study (LIS), 2022)
Despite the steady increase in the number of women who join the labor force, there are still substantial cross-country variations in both women's labor force participation and gender-linked occupational inequality. Utilizing micro-data from 47 countries (circa 2013) obtained from the Luxembourg Income Study, we examine the extent to which globalization and each of its three components (economic, social and political) affect gender-based economic inequality. In particular, we investigate the effect of globalization on two outcomes: women's labor force participation and women's relative odds of obtaining high-income, high-status jobs. The findings show, first, that social globalization is more consequential for gender inequality in the labor market than either economic or political globalization. Second, while social globalization increases women's labor force participation, it reduces women's relative odds of obtaining lucrative, high-status jobs. The findings are discussed in light of the comparative literature on gender-based inequality.
Keywords: 330; Occupational sex segregation; Globalization; Gender; Labor markets; multilevel models